THEORETICAL APPROACHES TO ETHNO-PSYCHOLOGICAL AND CROSS-CULTURAL STUDIES OF SUBJECTIVE WELL-BEING OF THE PERSONALITY - R M Shamionov (Peoples' Friendship University of Russia (RUDN University), 2016)
The article gives a consistent analysis of the conceptual approaches to studying the psychological (cultural) conditionality of subjective well-being. There are differences in the definition and understanding of subjective well-being, due to the commitment of foreign and domestic researchers to different theoretical trends. The issues of compatibility of different approaches to harmonizing them are discussed in the article. It is proposed to consider subjective well-being as a dynamic system with multiple and multi-level determination. The ethno-cultural determination of subjective well-being should be considered together with the general social, psycho-physiological, age and the others. A relative similarity of the approaches to ethno-psychological and cross-cultural studies of well-being by the Russian and foreign researchers, as well as a tendency to reconcile the various aspects of well-being in empirical research are noted in the article. The theoretical tasks necessary for the unification of the results of empirical research are determined.